Human Resource Management in Policing Fraud - Dirin, Dirin; Handriatmo, Yuyun Arief Kus; Kesuma, Dicky Irawan; Setyawan, Nugroho Ari (Association of Certified Fraud Examiners Indonesia Chapter, 2023)
This paper draws on the roles of Human Resource Management (HRM) in policing fraud by the Indonesian National Police (INP). The method of this study is a literature review and document analysis.Â This research finds that HRM has a role in policing fraud through 1) recruitment, 2) education, 2) use/development, 3) maintenance and 4) termination from the office. HRM is potentially essential for improving police professionalism. Further, the HRM success application may cause the success of bureaucracy and governance reform for corruption prevention in the INP. Moreover, operational policing fraud can be improved by reliable HRM practices. Next, this paper suggests a further empirical study to explore HRM in policing and its role in policing fraud.